Analysis of Heavy Equipment Productivity in Normalization and Embankment Work in Sei Berapit Indragiri Hilir Regency - Doni Yudia Saputra; Zainuri Zainuri; Fitridawati Soehardi (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2026)
The 30% delay in construction progress on the Normalization and Embankment Construction project in Sei Berapit, Indragiri Hilir Regency, where as of the last week of November 2025 only 70% of the work had been completed, indicates that heavy equipment productivity has not met the planned target. This study aims to analyze the productivity of amphibious excavators and determine the effective number of equipment alternatives to accelerate project completion. The method used is a quantitative method with a case study approach, with productivity analysis based on work cycle time data, equipment efficiency, and actual production capacity from field observations. The analysis results show that in Alternative I, namely the use of two amphibious excavators, daily production capacity increased significantly to around 980,627 m³/day, so that the remaining work volume of 5,760.416 m³ could theoretically be completed in around 6 working days. This increase in productivity not only has an impact on accelerating the duration of implementation but also provides better operational flexibility in anticipating field disruptions. Compared to other equipment addition alternatives, Alternative I is considered the most rational because it reduces unproductive time, minimizes the risk of delays due to equipment damage or other operational disruptions, and remains within an acceptable daily operational cost level of IDR. 27,363,200. This finding confirms that productivity control and determining the number of amphibious excavators play a crucial role in time and cost management. Therefore, heavy equipment productivity evaluation should be conducted from the project planning stage, especially for excavation work in flooded terrain, to ensure optimal achievement of implementation targets.